Weighted composition operators between growth spaces of the upper half-plane - Stević, Stevo; Sharma, Ajay K. (Utilitas Mathematica, 2011)
Let ψ be a holomorphic map of the upper half-plane Π+ and φ be a holomorphic self-map of Π+. We characterize bounded weighted composition operators acting between growth spaces of the upper half-plane. Under some conditions on φ and ψ, we also characterize compact weighted composition operators between growth spaces of the upper half-plane.